Temporal Variability and Ecological Interactions of Parasitic Marine Syndiniales in Coastal Protist Communities - Sean R. Anderson (American Society for Microbiology, 2020)
ABSTRACT Syndiniales are a ubiquitous group of protist parasites that infect and kill a wide range of hosts, including harmful bloom-forming dinoflagellates. Despite the importance of parasitism as an agent of plankton mortality, parasite-host dynamics remain poorly understood, especially over time, hindering the inclusion of parasitism in food web and ecosystem models. For a full year in the Skidaway River Estuary (Georgia), we employed weekly 18S rRNA sampling and co-occurrence network analysis to characterize temporal parasite-host infection dynamics of Syndiniales. Over the year, Syndiniales exhibited strong temporal variability, with higher relative abundance from June to October (7 to 28%) than other months in the year (0.01% to 6%). Nonmetric dimensional scaling of Syndiniales composition revealed tight clustering in June to October that coincided with elevated temperatures (23 to 31°C), though in general, abiotic factors poorly explained composition (canonical correspondence analysis [CCA] and partial least-squares [PLS]) and were less important in the network than biotic relationships. Syndiniales amplicon sequence variants (ASVs) were well represented in the co-occurrence network (20% of edges) and had significant positive associations (Spearman r > 0.7), inferred to be putative parasite-host relationships, with known dinoflagellate hosts (e.g., Akashiwo and Gymnodinium) and other protist groups (e.g., ciliates, radiolarians, and diatoms). Positive associations rarely involved a single Syndiniales and dinoflagellate species, implying flexible parasite-host infection dynamics. These findings provide insight into the temporal dynamics of Syndiniales over a full year and reinforce the importance of single-celled parasites in driving plankton population dynamics. Further empirical work is needed to confirm network interactions and to incorporate parasitism within the context of ecosystem models. IMPORTANCE Protist parasites in the marine alveolate group, Syndiniales, have been observed within infected plankton host cells for decades, and recently, global-scale efforts (Tara Ocean exploration) have confirmed their importance within microbial communities. Yet, protist parasites remain enigmatic, particularly with respect to their temporal dynamics and parasite-host interactions. We employed weekly 18S amplicon surveys over a full year in a coastal estuary, revealing strong temporal shifts in Syndiniales parasites, with highest relative abundance during warmer summer to fall months. Though influenced by temperature, Syndiniales population dynamics were also driven by a high frequency of biological interactions with other protist groups, as determined through co-occurrence network analysis. Parasitic interactions implied by the network highlighted a range of confirmed (dinoflagellates) and putative (diatoms) interactions and suggests parasites may be less selective in their preferred hosts. Understanding parasite-host dynamics over space and time will improve our ability to include parasitism as a loss term in microbial food web models.